Skillful Swimming in Age-Groups Is Determined by Anthropometrics, Biomechanics and Energetics - Barbosa, Tiago M.; Bartolomeu, Raul; Morais, Jorge E.; Costa, Mário J. (Frontiers in Physiology, 2019)
The aim was to compare the anthropometrics, biomechanics and energetics in young swimmers of different competitive levels. Seventy-five boys aged between 11 and 13 years-old with a broad range of performances were ranked based on their personal best time in the men’s 100m freestyle event and then split-up into three tiers (Tier-1, i.e., top-tier, best performers; Tier-2, mid-tier; Tier-3, lower-tier). A set of anthropometric features was measured (height, body mass, arm span and trunk transverse surface area). Stroke kinematics (speed, stroke length, stroke frequency) was assessed by a Speedo-meter. Swim efficiency was then estimated (stroke index, speed fluctuation, Froude efficiency). Hydrodynamics assessment encompassed the estimation of active drag and drag coefficient by velocity perturbation method and a set of dimensionless numbers (Froude, hull speed, Reynolds). Mechanical power (to overcome drag, transfer of kinetic energy to water, external power) and power input were derived. There was a significant variation with moderate effect sizes in all anthropometric features but the trunk transverse surface area. Tier-1 swimmers were taller, heavier and with longer limbs than remaining counterparts. There were also significant variations in the stroke kinematics with moderate-large effect sizes. Tier-1 swimmers showed higher stroke frequency, stroke length, speed, stroke index and propelling efficiency but lower speed fluctuations. Reynold number, Froude number and hull speed were significantly higher in Tier-1 swimmers, denoting large effect sizes. The mechanical power and power input delivered were significantly higher in tier-1 swimmers, showing moderate effect sizes. As a conclusion, it was noted significant variations, with moderate-large effect sizes, among the three tiers, for the vast majority of the selected variables. The better performances by tier-1 swimmers were related to their anthropometrics, biomechanics and energetics.